Photosynthetic limitations in mediterranean plants: A review - Flexas, J.; Diaz-Espejo, a; Gago, J.; Gallé, a; Galmés, J.; Gulías, J.; Medrano, H.; Díaz-Espejo, A. (Environmental and Experimental Botany, 2013)
The aim of the present work is to review the literature concerning photosynthesis of Mediterranean plants. First, we briefly review the most important environmental constraints to photosynthesis, i.e. chilling winter temperatures and summer drought. Then, the review specifically focus on the photosynthetic capacity and photosynthetic limitations of Mediterranean plants under non-stress conditions, to test the general assumption that that the photosynthetic capacity of Mediterranean plants is lower than that of plants from other biomes. It is shown that Mediterranean plants of different life forms and leaf types present, on average, similar photosynthetic capacity to plants from any other biome. However, the mechanisms potentially limiting maximum photosynthesis differ between Mediterranean and non-Mediterranean species. For instance, Mediterranean plants compensate their lower mesophyll conductance to CO2 (gm) with a larger velocity of carboxylation (Vc,max) to achieve similar photosynthesis rates (AN) to non-Mediterranean plants, both factors being associated to a larger leaf mass area (LMA) in Mediterranean species. In contrast, stomatal conductance (gs) was found to be lower only in Mediterranean sclerophytes. On the other hand, Mediterranean sclerophytes and malacophytes (but not herbs and mesophytes) show higher mean intrinsic water use efficiency (AN / gs) due to a combination of higher gm / gs and AN per unit CO2 concentration in the chloroplasts, i.e. carboxylation efficiency. represent specific adaptations of Mediterranean plants to their environment, leading these plants to achieve high AN despite their large LMA, and Mediterranean ecosystems to be Accepted Manuscript The described variations in the mechanistic components of photosynthesis may among those presenting the largest net primary productivities worldwide
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: biochemical limitation; chilling; Drought; Mediterranean; mesophyll conductance limitation; stomatal limitation